Pencegahan Risiko Lingkungan dalam Skala Mikro Permukiman (Studi Kasus Rt 8 Rw4 Malaka Jaya Duren Sawit Jakarta Timur) - Supriadi, Taufiq; Sari, Novena Kristina; Permadi, Bagus; Sari, Lintang Lasmita (Jurnal Ar Ro'is Mandalika (Armada), 2026)
This study examines environmental risk prevention at the micro-scale in densely populated residential areas, specifically focusing on RT8 RW4 Malaka Jaya in Duren Sawit, East Jakarta. Rapid urbanization, limited space, and the dominance of concrete structures in the area have led to several environmental risks, including poor drainage systems, waste mismanagement, and reduced green spaces. This research employs a qualitative methodology, including field observation, interviews with local leaders, and literature review, to understand the environmental risks faced by the community. The study highlights the role of community-based innovations in managing these risks, such as the transformation of drainage channels into fish farming ponds, waste management through communal composting, and the use of solar energy. The findings suggest that these initiatives, driven by local leadership and active community participation, have proven effective in mitigating environmental risks and improving the living conditions of residents. The research also discusses the importance of involving local governance units like RT in environmental management, particularly in urban areas facing limited resources. These findings contribute to the understanding of how community-based environmental management approaches can address urban environmental challenges.